NEUROMARKETING IN DESTINATION: A SYSTEMATIC LITERATURE REVIEW - Iskandar, Rizal; Rahmattullah, Muhammad; Amima, Sharfina Puteri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
This study aims to explore the development of neuromarketing research in the tourism sector between 2017 and 2024. The research method employed is a systematic literature review (SLR) developed by Kitchenham and Charters, which analyzes articles published in ScienceDirect, DOAJ, Emerald, EconPapers, and SpringerLink. The study's findings indicate that the use of neuromarketing in tourism remains limited, primarily focusing on analyzing advertising types, such as photos and videos, and predominantly utilizing eye-tracking. Additionally, we found that the technology most commonly used to observe brain activity is the electroencephalogram (EEG), rather than Functional Magnetic Resonance Imaging (FMRI). Future research suggests that neuromarketing could become a marketing trend in tourism, potentially influencing consumer decision-making and allowing for the tracking of consumer happiness levels.